Prostate cancer with metastasis in the fibula. Presentation of a Case. - Horacio Suárez Monzón; Rolando Delgado Figueredo; Santiago Palacio Pérez (Medisur)
The case of a 70 years old patient of masculine sex is presented. After having suffered a traumatism in the left inferior limb and having fulfilled the suitable treatment, the patient presented new signs and symptoms that led him to the department of Orthopedics and Traumatology. With the initial exams and treatment no improvement was obtained, thus doctors decided to opt for the surgical treatment. It could be observed the presence of an osteolytic lesion of approximately 5 cm and the pertinent samples were taken to carry out biopsies of the muscle and the bone. Results didn't lead to a definitive diagnosis. The result of new exams required an inter-consult with the Service of Urology, to obtain the diagnosis of prostatic adenocarcinoma. The revision of the national and international literature didn't report any similar case; the atypical localization of the metastasis is what led to the preparation of the case for its knowledge and diffusion, for what it can contribute to the experience of professionals specialized in orthopedics or urology.